Ethmolaimus riparius sp. n. and Paramononchus major sp. n. (Nematoda) from Lake Baikal, Russia - Gagarin, Vladimir G.; Naumova, Tatyana V. (Zootaxa, 2016)
Two new nematode species found in Lake Baikal (Russia) are described and illustrated. Ethmolaimus riparius sp. n. is morphologically close to E. pilosus Shoshin, 1998 and E. lanatus Shoshin, 1998. The new species differs from E. pilosus by the longer and thinner body (L = 1228–1501 µm, a = 26–34 vs L = 720–1070 µm, a = 19–23), larger stoma (26–32 µm long vs 19–24 µm long), longer spicules and gubernaculum (45–50 µm long and 21–25 µm long vs accordingly 32–37 µm long and 8 µm long). E. riparius sp. n. differs from E. lanatus by the longer body (L = 1228–1501 µm vs L = 680–1180), shorter cephalic setae (its length is equal 1.1–1.4 labial region diameter vs 1.6–2.1 labial region diameter) and longer spicules and gubernaculum (45–50 µm long and 21–25 µm long vs accordingly 25–30 µm long and 7–8 µm long). Paramononchus major sp. n is close to P. orientalis Gagarin & Naumova, 2012, but differs from it by the longer body (L = 5926–7820 µm vs L = 3081–3778 µm), longer spicules (410–475 µm long vs 208–238 µm long) and larger number of precloacal supplements (52–61 vs 21–24). Keys for the identification of valid species of the genera Ethmolaimus and Paramononchus are given.